Characterization of polysaccharides from wild edible mushrooms from Thailand and their antioxidant, antidiabetic, and antihypertensive activities - Khwanta Kaewnarin (2020)
© 2020 by Begell House, Inc. Bioactive polysaccharides from three wild edible mushrooms (Rugibolutus extremiorientalis, Russula emetica, and Phleobopus portentosus) extracted by conventional refluxing extraction (RFE) and ultrasound-assisted extraction (UAE) were investigated. The result indicated that the PS of R. extremiorientalis extracted by RFE exhibited the greatest antioxidant activities on ABTS cation free radical scavenging (153.0 mg TEAC/g of the extract), DPPH radical scavenging (9.91 mg TEAC/g of the extract), and also reducing power capacity (10.2 mg TEAC/g of the extract). Whereas, those of R. emetica extracted by UAE have the highest antidiabetic and antihypertensive activities (56.3% and 70.5% inhibition, respectively). All crude PS extracts were composed mainly of carbohydrate and protein plus a small proportion of phenolic compounds of which glucose was the prevalent monosaccharide of all polysaccharides. PS of both R. extremiorientalis and R. emetica contained of β-glycosidic conformation, while those of Ph. portentosus contained both α-and β-glycosidic conformations.